KEUTAMAAN ILMU DAN ULAMA PERSPEKTIF HADITS SHOHIH BUKHORI NO HADITS 100 DAN RELEVANSINYA BAGI PENDIDIKAN GEN-Z - Andi Setiawan; Shobihus Surur (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This thesis explores the essence of the Virtue of Knowledge and Ulama as reflected from the Hadith perspective, especially in the Shohih Bukhori Book No. Hadith 100, and comprehensively reviews its relevance in Gen-Z education. This research summarizes the essence of the values embedded in the Hadith text to explore the deep meaning of the primacy of science and ulama in education. The research method used is maudlu'i with a qualitative approach, which allows in-depth analysis of the context and implications of the Priority of Science and Ulama perspective on hadith. Shohih Bukhori Hadith No. 100 was chosen as the main focus because this hadith provides a strong foundation for the principles of learning, and the importance of the primacy of knowledge and scholars in education.The research results show that the Koran is not only a source of religious teachings, but also offers views on human diversity and the values that must be instilled in education. The priority of science and scholars in education inspired by Hadith requires a learning approach that focuses on respect for educators, religion and the values that exist in society. This research provides in-depth insight into the application of the priority of science and scholars in education in the context of Islamic education. This includes curriculum development, learning methods that focus on respect for educators, as well as the formation of attitudes and skills for students. This thesis contributes significantly to understanding the importance of science education in Islam and provides practical guidance for developing education according to the teachings of the Koran